Effectiveness of Academic Integrity in the Age of AI in Sri Lankan Higher Education Sector: Challenges and Solutions - Nuskiya, M.H.F.; Ruzaik, Fareena (University of Colombo, 2024)
The rapid integration of artificial intelligence (AI) into higher education has revolutionized teaching and assessment practices, yet it has also presented significant challenges to maintaining academic integrity. The study focuses on higher education institutions in Sri Lanka. The purpose of this study is to analyse the effectiveness of academic integrity practices in the context of AI technologies within the higher education sector of Sri Lanka. Specifically, it examines AI-driven assessment methods, concerns about plagiarism detection tools, and the effectiveness of current certification methods in preserving academic integrity. A structured online questionnaire was administered to 147 participants from diverse academic backgrounds and institutions across Sri Lanka. Quantitative data were collected through extracted from Likert-scale responses and demographic data. Hypothesis tests including the chi-square test and ANOVA were used to assess the statistical significance of differences in perceptions among demographic variables. The survey findings suggest mixed views on the effectiveness of academic integrity practices ...
Keywords: Artificial Intelligence; Academic Integrity; Higher Education; Assessment Methods; Plagiarism Detection